Hubungan Karakter Disiplin Dan Motivasi Peserta Didik Dengan Hasil Belajar Kognitif Akidah Akhlak Kelas VIII MTs NU Hasyim Asy’ari 2 Kudus - Maya Sari, Vivin Novita; Auliya, Nanang Nabhar Fakhri (Education Mind Based Development Association, 2023)
The study aims to determine the disciplined character of students in the moral aqidah at MTs NU Hasyim Asy’ari 2 Kudus. To find out the motivation of students in the moral aqidah at MTs NU Hasyim Asy’ari 2 Kudus. To find out cognitive learning outcomes in moral aqidah at MTs NU Hasyim Asy’ari 2 Kudus. To find out there is a positive relationship between the character of discipline and motivation of students with cognitive learning outcomes in the moral aqidah at MTs NU Hasyim Asy’ari 2 Kudus. This type of research is quantitative research with quantitative data sources with a view to studying the relationship between two or more variables. Data collection techniques used was simple random sampling technique. The sample is this study were all students of class VIII at MTs NU Hasyim Asy’ari 2 Kudus, totaling 108 students. The data analysis technique uses the validity and reliability test of the instrument, the classical assumption test, and the hypothesis test. The results showed that the disciplined character of student in the moral aqidah had an average value of 81.3810, this value was included in the interval range 70 < X < 93, meaning that the character of discipline students in the moral aqidah at MTs NU Hasyim Asy’ari 2 Kudus are in the medium category. The motivation of students in the moral aqidah subjects has an average value of 86.7381, the value is included in the interval range of 77 < X < 96, meaning that the motivation of students is in the medium category. Cognitive learning outcomes of students on the subject of moral aqidah have an average value of 90.8929, the value is included in the interval range of 83 < X, meaning that the cognitive learning outcomes of students are in the high category. There is a positive relationship between the character of the discipline and motivation of students with cognitive learning outcomes in the subjects of moral aqidah at MTs NU Hasyim Asy'ari 2 Kudus. Based on the calculated F value > F table, that is (4,121>3.11). Supported by a significance value smaller than 0.05, which shows a value of 0.013.